Brain–Heart Axis: Brain-Derived Neurotrophic Factor and Cardiovascular Disease—A Review of Systematic Reviews - Massimo Fioranelli; Maria Luisa Garo; Maria Grazia Roccia; Bianca Prizbelek; Francesca Romana Sconci (Life, 2023)
Background: The brain–heart axis is an intra- and bidirectional complex that links central nervous system dysfunction and cardiac dysfunction. In recent decades, brain-derived neurotrophic factor (BDNF) has emerged as a strategic molecule involved in both brain and cardiovascular disease (CVD). This systematic review of systematic reviews aimed to (1) identify and summarize the evidence for the BDNF genotype and BDNF concentration in CVD risk assessment, (2) evaluate the evidence for the use of BDNF as a biomarker of CVD recovery, and (3) evaluate rehabilitation approaches that can restore BDNF concentration. Methods: A comprehensive search strategy was developed using PRISMA. The risk of bias was assessed via ROBIS. Results: Seven studies were identified, most of which aimed to evaluate the role of BDNF in stroke patients. Only two systematic reviews examined the association of BDNF concentration and polymorphism in CVDs other than stroke. Conclusions: The overall evidence showed that BDNF plays a fundamental role in assessing the risk of CVD occurrence, because lower BDNF concentrations and rs6265 polymorphism are often associated with CVD. Nevertheless, much work remains to be carried out in current research to investigate how BDNF is modulated in different cardiovascular diseases and in different populations.